Production and strenght of fiber reinforced arch pan as permenent formwork for floor slabs - Muhammad Fizree , Ghazali (2015)
Nowadays, the methods and cost of construction rapidly change parallel to the current technology development. The application of the permanent formwork will reduce the time consumption and the number of workers for a certain construction project. This is due to the reduction of working load on site. The advantage of the permanent formwork is where the formwork will become a part of the structure. Other than that, the replacement of the temporary formwork will reduce the construction waste during construction. The purpose of this research is to identify the materials, to fabricate and also to determine the strength of fibre reinforced arch pan as a permanent formwork. The scopes of this research are focused on the materials and cost of producing the arch pan as permanent formwork for the slabs and also included laboratory testing for the sample to get the strength characteristic of the structure. This research is to determine the optimal strength of arch pan under uniformly distributed load from the slab and to achieve the required load of 100kg or 1000N of concrete arch pan without cracking. Kenaf fibers were laid inside the length of the concrete arch pan which acts as a flexural reinforcement. Based on the arch pan design calculation, the maximum height of arch pan is 75mm and the required load for the concrete arch pan has successfully passed without cracking. The strength of concrete arch pan increases with the use of kenaf fiber as a reinforcement.